Математическое моделирование температурного поля в материале при резании - Флоров, А. В. (НТУ "ХПИ", 2012)
In this article we examine the necessity of creating more simple technique for calculation of temperatural field which will help to detect temperatural deformations in a tool and blank. Here it’s offered a new methodical way of the temperatural field detection in material by the example of cutting tool.
Keywords: обработка механическая; управление числовое; управление программное; деформация тепловая; теплопроводность; резец